Nushagak: an historic trading center in southwestern Alaska / Fieldiana, Anthropology, v. 62 - VanStone, James W.; Williams, Patricia M. editor Managing Editor, Scientific Publications ([Chicago] Field Museum Press, 1972)
Includes bibliographical references (p. 87-90). Fieldiana series has been published as Anthropological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Anthropology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).